Comunidades de aves de sub-bosque de remanescentes florestais de mata atlântica do nordeste do Brasil: composição, diversidade e hábitat. - Melo, Daniela de Carvalho (2013)
Ecological analysis of the structure of understory bird communities of forest remnants of Atlantic Forest of Paraíba. South America is the region with the highest bird diversity in the world. The Atlantic Forest biome in Brazil is the second most diverse. Its portion in Paraíba integrates Pernambuco Endemism Centre, a region that is home of two-thirds of the bird species present in the biome. The present study investigated the bird communities in the understory of three Atlantic Forest remnants of Paraíba through the method of capture with mist nets. Ten nets were positioned in the forest understory in eight different points in each remnant, in a summit of 48 day samples, in a total effort of 2.895 hours-net. A total of 333 specimens of 44 species were captured, divided into 19 families. The recapture rate was 2%. The species with the highest representation were Arremon taciturnus (n = 40), Chiroxiphia pareola (n = 32) and Conopophaga melanops (n = 28), the latter being an endemic species considered as threatened in the Atlantic Forest with the status of vulnerable . Endangered species totaled 16% of the records and the same value was found for the endemic. Species richness among the three remnants did not differ (χ² = 0.667, d.f = 2, p = 0.7165), and according to the communities of birds found, diversity was considered low, with a predominance of dominant and generalists species. The species composition was little similar among the remnants, suggesting that the size, matrix and the availability of different microhabitats in each remnant may have influenced the species presence. The Reserva Particular do Patrimônio Natural Engenho Gargaú remnant was the one with the highest number of endemic and threatened species, as well as with the most understory insectivores, thus suggesting that this remnant is best conserved.